Innovation in Environmentally Friendly Materials: Making Paralon Soprano Alto Tenor Bass (SATB) Musical Instruments - Phetorant, Dimas; Kusnawan, Uus (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2023)
This study seeks to explore the paralon's ability to make musical instruments. Paralon is a material that is strong against weather changes. The novelty of this research is in the form of the soprano, alto, tenor, and bass (SATB) paralon musical instrument. For this reason, researchers describe and explore the tool step by step until its presentation. The purpose of this study was to find innovations in making musical instruments from paralon. This study uses a qualitative method along with exploration. Data were collected through observation, interviews, and literature studies as reference materials related to this research. Observations were carried out by researchers by observing the making of the SATB paralon musical instrument, measuring the parts of the paralon, and taking notes. Exploration of the internet for literature to add insight about the object to be studied. The stages of making the SATB paralon musical instrument begin with finding the raw materials to be used. After all the raw materials are obtained, the paralon pipe is cut and shaped according to the design that the researcher made. Followed by installing a knife at the end of the paralon. After gluing, the process of finding the tone (tuning) of the paralon pipe begins. The table is needed to place the SATB paralon musical instrument, which is made and shaped according to the SATB paralon musical instrument.